A Study of Pragmatic Features of Parallelism Used in English and Vietnamese Advertising Slogans - Phạm Thị Thúy (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis is aimed to study the pragmatic features of parallel structures used in English and Vietnamese advertising slogans. The findings of the study could help learners of English and Vietnamese and companies have a better insight into parallelism and its effects on designing advertising slogans